NILAI PENDIDIKAN YANG TERKANDUNG DALAM ADAT ISTIADAT MANDI SAFAR DIDESA TELUK LECAH, KABUPATEN BENGKALIS PROVINSI RIAU - Juliana, Juliana; Oktavia, Khairani; Ismail, Ismail (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
The research method used is a qualitative method with observation and interview techniques with selected informants with a purposive sample. The results of the study show that safar bathing is a tradition that is still maintained by the local community today as a sign of gratitude for the smooth running of daily activities and as an opportunity to purify oneself spiritually. Safar bathing procedures include the preparation of materials, and ceremonies, as well as handing over the yellow rice to the villagers. Bathing is done alternately with water taken from water sources that are considered sacred. Mandi Safar in Teluk Lecah Village has important social, cultural and religious values ​​for the local community